Kajian modifikasi unit reforming pabrik amoniak pusri iii dan kajian pemanfaatan gas paduser sebagai bahan bakar pengganti gas alam di pt pupuk sriwidjaja - J Junaedi; Herri Susanto; Benny Haryoso (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2006)
Study of reforming unit modification of ammonia plant Pusri iii and gas producer utilization as subtitution fuel for natural gas in PT Pupuk Sriwidjaja. This study dealt with an energy conservation program at the reforming unit in PT Pupuk Sriwidjaja, to anticipate the increase of price and possible shortage of natural gas in the nearfillure. A potential reduction of natural gas consumption was evaluated based on thermodynamic modeling and simulation. Three process modifications were studied and their performance had heen compared to the existing unit: KRES (KBR Reforming Exchanger System); totally replace the existing primary reformer; ATR (AutoThermal Reformer): totally replace the existing primary reformer; KRES-revamp: appending KRES on the existing unit. Compared to that of the existing reformer of 37.15 MMBtu/metric ton of NH3 the natural gas consumption in the proposed modified process are lower by 9%, 15%, and 20% in KRES-revamp, KRES. and ATR, respectively. Unfortunately, the proposed modified process produces less steam as by-product due to the decrease of waste sensible heat. Therefore, to restore the steam supply, the proposed modified process requires an additional auxiliary boiler with a capacity of 105 tons/hour for KRES-revamp, 137 tons/hour for KRES and 97 tons/hour for ATR. KRES-revamp has been considered as the most attractive modification. This modification may give an annual natural gas saving of about 8.39%. In addition based on investment aspect. KRES-revamp is very attractive due to payback period of about 10 months. The use of producer gas (produced from the gasification of coal) as a substitute of natural gas for fuel was found to be thermodynamically feasible. But a separate study shows that the producer gas price is about 5 USD/MMBtu. Thus, the use of producer gas was not attractive yet economically. Moreover, the producer gas consumption combined with natural gas is higher than natural gas only (37,26 vs. 34,86 MMBtu/metric ton of NH3 with some modifications in combustion system.Keywords: reforming unit, producer gas and energy efficiency. AbstrakSehuhungan dengan kecenderungan kenaikan harga dan ketidakpastian pasokan gas alam, PT Pupuk Sriwidjaja telah menyusun rencana penghematan konsumsi gas alam dengan modifikasi proses maupun pemanfaatan batubara sebagai bahan bakar alternatif. Penelitian dilakukan terhadap empat konfigurasi existing unit yang terdiri dari primary and secondary reformers, KRES yang berupa unit baru pengganti existing unit, ATR yang berupa unit baru pengganti existing unit, KRES-revamp yang menggahung KRES dengan existing unit. Secara termodinamika, teknologi produksi gas sintesis KRES-revamp, KRES. ATR terbukti lebih efisien dan dapat mengurangi konsumsi gas alam untuk pabrik amoniak berturut-turut: 9%, 15%. dan 20% dari kebutuhan gas alam untuk reformer konvensional sebesar 37,15 MMBtu/MT NH3. Walaupun efisiensi energi lebih baik, teknologi-teknologi tersebut juga memerlukan modifikasi steam system dan mengakibatkan penambahan auxiliary boiler dengan kapasitas berturut-turut: 105, 137, dan 97 ton/jam. Selanjutnya kajian diperdalam untuk KRES-revamp. Penerapan KRES-revamp dengan kapasitas produksi amoniak tetap 1200 MTPD (kasus yang pertama) dapat menurunkan biaya produksi hingga 8,39%/tahun. Hanya dengan memperhatikan investasi untuk tambahan KRES dan tambahan auxilliary boiler, Payback Period diperkirakan 10 bulan. Substitusi gas alam dengan gas produser untuk saat ini kurang menarik karena menurut kajian lain harga gas hasil gasifikasi diperkirakan mencapai 5 USD/MMBtu (pada kondisi tertentu). Terlebih lagi pemanfaatan gas produser sebagai bahan bakar pengganti gas alam memerlukan beberapa modifikasi pada sistem pembakaran. Di samping itu, konsumsi total energi gabungan gas alam dan gas produser lebih tinggi daripada yang hanya gas alam (37,26 vs. 34,86 MMBtu/MT NH3.Kata kunci: Reforming unit, Gas produser, Efisiensi Energi.